Bioactive whey peptides: a bibliometric and functional overview - Eduarda Heck Sumny; Aniela Pinto Kempka (Discover Food)
Abstract The objective of this research was to examine bioactive peptides derived from whey, focusing on their functional properties and potential applications in food and therapeutics. The research began with a bibliometric analysis, mapping scientific progress and research trends related to these peptides, particularly in key areas such as antioxidant and antihypertensive activities. Subsequently, a systematic literature review was conducted to investigate extraction and purification methods, as well as the biological activities of whey peptides, including their ability to inhibit angiotensin-converting enzyme, modulate the immune system, and act as antimicrobial agents. The findings revealed that whey peptides, primarily obtained through the enzymatic hydrolysis of proteins such as lactalbumin and lactoglobulin, have a significant capacity to neutralize free radicals, thereby reducing oxidative stress, a key factor in preventing chronic diseases such as cardiovascular disorders and cancer. Additionally, there is increasing interest in incorporating these peptides into functional foods due to their health benefits beyond basic nutrition. The bibliometric analysis indicated that this research area is expanding rapidly, with the potential to influence the development of novel food products that integrate nutrition and therapeutic benefits. Advances in extraction technologies and applications of whey peptides could drive major innovations in food biotechnology, reinforcing the need for further research to fully explore the potential of these bioactive compounds.